Social Responsibility and Governance-Management Process as a Basis of Excellence in Public Administration - Nina Tomaževič (Central European Public Administration Review)
An increasing number of public administration organisations are already aware of the fact that excellence is not only the domain of private sector organisations. They are looking for up-to-date management tools with which they would like to continuously improve operations and increase stakeholder satisfaction. This confirms the belief that approaches for managing private organisations are the same as for public organisations, the only difference (by now) being in the basic goal(s) of private and public sector organisations. The article presents definitions and descriptions of key fields whose understanding is important for the logical and systematic formation and use of an up-to-date excellence model for public administration. The proposed excellence model was formed and tested with the objective to contribute to the development of Slovenian public administration and a state as a whole.